The Integration of Global Positioning System (GPS) and meteorological observations for tropospheric model development in Malaysian region - Kamarudin, Md. Nor; Wan Mohd. Akib , Wan Abdul Aziz; Che Awang, Mohamad Saupi; Mohd. Zaki , Mohd. Zahlan; Subari, Mustafa Din (UTM, 2006)
The use of satellite based Global Positioning System (GPS) is normal in engineering and surveying for a wide range of applications as the accuracy capability increases. Global Positioning System (GPS) satellites provide precise all weather global navigation information to users equipped with GPS receivers on or near the earth’s surface. The GPS satellites transmit signals that are received by the receivers on the earth’s surface to determine the position. The effects of other different error sources on the computed position have to be removed from the data. The principal limiting error source is incorrect modeling of the delay experienced by GPS signal propagating through the electrically neutral atmosphere, usually referred to as the tropospheric delay. The integration of ground based meteorological observations and GPS lead to a better understanding of the tropospheric delay to the GPS signal and improve the GPS height accuracy. The study conducted by integrating the Malaysian Active GPS Station (MASS) data and ground based meteorological observations to analyze the variation occur to the GPS height determination due to the tropospheric delay. The introduction of the Saastamoinen tropospheric model to the data shows a delay variation for up to 20 meter in pseudorange which causes an error up to 5 meter of height component. Processing with certain tropospheric delay correction model using synchronizes ground meteorological and GPS data at the same point can provide better accurate baseline.